H-ferritin ferroxidase induces cytoprotective pathways and inhibits microvascular stasis in transgenic sickle mice - Vercellotti, Gregory M.; Khan, Fatima B.; Nguyen, Julia; Chen, Chunsheng; Bruzzone, Carol M.; Bechtel, Heather; Brown, Graham; Nath, Karl A.; Steer, Clifford J.; Hebbel, Robert P.; Belcher, John D. (Frontiers in Pharmacology, 2014)
Hemolysis, oxidative stress, inflammation, vaso-occlusion, and organ infarction are hallmarks of sickle cell disease (SCD). We have previously shown that increases in heme oxygenase-1 (HO-1) activity detoxify heme and inhibit vaso-occlusion in transgenic mouse models of SCD. HO-1 releases Fe2+ from heme, and the ferritin heavy chain (FHC) ferroxidase oxidizes Fe2+ to catalytically inactive Fe3+ inside ferritin. FHC overexpression has been shown to be cytoprotective. In this study, we hypothesized that overexpression of FHC and its ferroxidase activity will inhibit inflammation and microvascular stasis in transgenic SCD mice in response to plasma hemoglobin. We utilized a Sleeping Beauty (SB) transposase plasmid to deliver a human wild-type-ferritin heavy chain (wt-hFHC) transposable element by hydrodynamic tail vein injections into NY1DD SCD mice. Control SCD mice were infused with the same volume of lactated Ringer’s solution (LRS) or a human triple missense FHC (ms-hFHC) plasmid with no ferroxidase activity. 8 weeks later, LRS-injected mice had 40% microvascular stasis (% non-flowing venules) 1 h after infusion of stroma-free hemoglobin, while mice overexpressing wt-hFHC had only 5% stasis (p < 0.05), and ms-hFHC mice had 33% stasis suggesting vascular protection by ferroxidase active wt-hFHC. The wt-hFHC SCD mice had marked increases in splenic hFHC mRNA and hepatic hFHC protein, ferritin light chain (FLC), 5-aminolevulinic acid synthase (ALAS), heme content, ferroportin, nuclear factor erythroid 2-related factor 2 (Nrf2), and HO-1 activity and protein. There was also a decrease in hepatic activated nuclear factor-kappa B (NF-κB) phospho-p65 and vascular cell adhesion molecule-1 (VCAM-1). Inhibition of HO-1 activity with tin protoporphyrin demonstrated HO-1 was not essential for the protection by wt-hFHC. We conclude that wt-hFHC ferroxidase activity enhances cytoprotective Nrf2-regulated proteins including HO-1, thereby resulting in decreased NF-κB-activation, adhesion molecules, and microvascular stasis in transgenic SCD mice.